Immigration conseling in an effort to incrase public awareness of reporting foreginers in region of imigration office class II TPI Cilegon: implementation of article 72 of law number 6 of 2011 - M. Ryanindityo; Fachrizza Sidi Pratama (Jurnal Abdimas Imigrasi, 2020)
As a form of increasing public understanding of immigration law and awareness to report on foreign nationals in their territory, the Directorate General of Immigration especially the Immigration Office has the obligation to conduct legal counseling to the people in their area, to assist in the oversight and implementation of article 72 of the law. number 6 in 2011. Especially after the issuance of presidential regulation number 21 of 2016 concerning visa-free visitation, where the addition of non-visa user countries automatically increases the number of foreign nationals entering Indonesia. Community understanding is highly expected regarding immigration functions and how they play a role in carrying out these functions. Collaboration on the role of immigration and related institutions especially the community is needed in carrying out supervision and reporting in order to uphold the country's sovereignty.